2004
DOI: 10.1084/jem.20040165
|View full text |Cite
|
Sign up to set email alerts
|

Compromised Function of Regulatory T Cells in Rheumatoid Arthritis and Reversal by Anti-TNFα Therapy

Abstract: Regulatory T cells have been clearly implicated in the control of disease in murine models of autoimmunity. The paucity of data regarding the role of these lymphocytes in human autoimmune disease has prompted us to examine their function in patients with rheumatoid arthritis (RA). Regulatory (CD4+CD25+) T cells isolated from patients with active RA displayed an anergic phenotype upon stimulation with anti-CD3 and anti-CD28 antibodies, and suppressed the proliferation of effector T cells in vitro. However, they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

56
883
13
31

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,131 publications
(994 citation statements)
references
References 30 publications
56
883
13
31
Order By: Relevance
“…Indeed, Treg cells from patients with active RA are defective in their ability to suppress proinflammatory cytokine production by activated Tcells and monocytes in vitro. Anti-TNFα Ab treatment significantly boosts the numbers of circulating Treg cells; the increase in Treg cells correlated with a reduction in CRP [39]. Further, TNFα blockade inhibits the expansion of human CD4 + VLA-1 + effector T cells in vitro, while augmenting the percentage of Treg cells in cultures [40].…”
Section: Effect On Immunoregulationmentioning
confidence: 89%
“…Indeed, Treg cells from patients with active RA are defective in their ability to suppress proinflammatory cytokine production by activated Tcells and monocytes in vitro. Anti-TNFα Ab treatment significantly boosts the numbers of circulating Treg cells; the increase in Treg cells correlated with a reduction in CRP [39]. Further, TNFα blockade inhibits the expansion of human CD4 + VLA-1 + effector T cells in vitro, while augmenting the percentage of Treg cells in cultures [40].…”
Section: Effect On Immunoregulationmentioning
confidence: 89%
“…These findings argue against an accumulation of T reg to the CNS during relapse and suggest that the functional alteration detectable in CD4 + CD25 high T cells from MS patients is not influenced by disease activity. However, studies with rheumatoid arthritis patients revealed thus far diverging results, showing either stable or reduced numbers of CD25 high regulatory T cells in the peripheral blood [39,40], therefore further studies regarding T reg distribution in active disease are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have demonstrated that Treg isolated from the peripheral blood of patients with RA show a defect in their ability to suppress pro-inflammatory cytokine production [16,17]. There does not appear to be a deficiency in the number of Treg in patients with RA except perhaps in the early phase of disease [18].…”
Section: Cytokine Blockade As a Methods Of Targeting Treg In Patientsmentioning
confidence: 85%